Investigating the synergistic effects of Metakaolin and silica fume on the strength and durability of recycled aggregate concrete at elevated temperatures - Imran Haider; Muhammad Yaqub; Inamullah Inam; Tariq Ali; Muhammad Zeeshan Qureshi; Nabil Ben Kahla; Anwar Ahmed; Hawreen Ahmed (Scientific Reports)
Abstract The use of recycled aggregate (RA) as a partial or full replacement of natural aggregate (NA) is a suitable method of concrete production that has positive impacts on the environment. However, recycled aggregate concrete (RAC) has relatively lower strength and durability than that of normal concrete. To improve concrete performance, silica-fume (SF) was added with 2.5% increment up to 7.5% and metakaolin (MK) is added with a 2.5% decrement from 15 to 7.5%. The concrete with 50% RA, 10% MK and 5% SF showed notable advancement in performance after 28 days of curing. At 28 days of curing, the concrete samples had 31.5 MPa compressive strength, 5.7 MPa splitting tensile strength, and 10.6 MPa flexural strength, a strength improvement of 5.19%, 16.47%, and 8.52% over control concrete. Ultrasonic pulse velocity (UPV) indicated a 16.13% increase alongside a 20.87% reduction in water absorption which confirmed stronger bond performance and better durability of modified concrete. RCA content influences acid resistance negatively when reaching 75% RCA shows maximum deterioration. In addition, the fire resistance of such concrete resulted in higher performance at different temperature conditions for the concrete. This is due to the small particles of silica fume and metakaolin which acted as major factors and led to performance enhancements by filling in the concrete matrix gaps. The combination provides affordable, sustainable construction alternatives. Experiments show that SCMs can produce high-performance recycled concrete for modern building construction.